PERSEPSI PENGGUNA FASILITAS ZONA SELAMAT SEKOLAH - Kusmaryono, Ismono; Rusgiyarto, Ferry; Widjajanti, Endang (Jurnal Transportasi, 2010)
School Safety Zone, as an instrument to reduce traffic speed in a school area, has been implemented in Indonesia. This study tried to evaluate the effectiveness of the School Safety Zone based on the perception of its users, including students, teachers, parents, and travelers around the school. The results show that most ofthe respondents understand very well the meaning and the purpose of the School Safety Zone. However, it is also found that âFour Tsâ method has not been recognized well by the respondents.Keywords: school safety zone, perception, Four Ts method